Chemical Constituents and Bioactivities of Azanza garckeana: A Review - Titus, Stephen Dio; Christian, Nelson; Samuel, Kennedy B.; Ishaya, Samuel G.; Francis, Achilus; Leyoa, Ajiduku Abershi (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
Azanza garckeana, commonly known as "Goron Tula," is a medicinal plant widely recognized in Southern Africa for its traditional applications in treating infertility, respiratory issues, and liver disorders. Recent studies have explored its bioactive compounds, revealing significant therapeutic potentials, such as antiplasmodial, antioxidant, anti-inflammatory, and uterotonic effects. Key phytochemicals like flavonoids, tannins, and alkaloids have been identified, contributing to its diverse pharmacological activities. This review compiles current knowledge on the chemical constituents and bioactivities of Azanza garckeana, providing a foundation for future research on its medicinal and nutritional applications. The plant's role in enhancing health, with potential uses in modern medicine, is also highlighted.